2020
DOI: 10.1038/s41419-020-2586-x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a new small-molecule inhibitor of HDAC6 in glioblastoma

Abstract: Histone deacetylase 6 (HDAC6) is an epigenetic modifier that is an attractive pharmacological target in cancer. In this work, we show that HDAC6 is elevated in glioblastoma, the most malignant and common brain tumor in adults, in which its high levels correlate with poor patient survival and is more abundant in glioma stem cell subpopulation. Moreover, we identified a new small-molecule inhibitor of HDAC6, which presents strong sensitivity for HDAC6 inhibition and exerts high cytotoxic activity, alone or in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 37 publications
0
30
0
3
Order By: Relevance
“…In combination with other anticancer drugs, HDAC6 inhibitor A542 suppresses the proliferation of follicular lymphoma (FL), chronic lymphocytic leukemia (CLL), germinal center diffuse large Bcell lymphoma cells (DLBCL) and CRC by targeting HDAC6 (86,87). Furthermore, HDAC6 inhibitors such as JOC1, SKLB-23bb, MPT0G413 as well as MPT0G612 show great anticancer activity, whereas the cytoplasm toxic as well as the mechanism are to be further investigated (68,(88)(89)(90)(91).…”
Section: Small Molecules Targeting Hats Hdacs and Brds In Cancer Thmentioning
confidence: 99%
“…In combination with other anticancer drugs, HDAC6 inhibitor A542 suppresses the proliferation of follicular lymphoma (FL), chronic lymphocytic leukemia (CLL), germinal center diffuse large Bcell lymphoma cells (DLBCL) and CRC by targeting HDAC6 (86,87). Furthermore, HDAC6 inhibitors such as JOC1, SKLB-23bb, MPT0G413 as well as MPT0G612 show great anticancer activity, whereas the cytoplasm toxic as well as the mechanism are to be further investigated (68,(88)(89)(90)(91).…”
Section: Small Molecules Targeting Hats Hdacs and Brds In Cancer Thmentioning
confidence: 99%
“…HDAC6 inhibitors can significantly reduce glioma cell proliferation by disrupting the G2/M transition, increasing cell death, and promoting cell cycle exit and tumor cell differentiation [ 1 , 7 , 8 ]. We first confirmed that our patient-derived L0 (high grade), S3 (high grade), and S7 (low grade) glioma cell lines are sensitive to HDAC6 inhibitors by treating dissociated cells in serum-free media with different concentrations of 1215 and 738.…”
Section: Resultsmentioning
confidence: 99%
“…Glioblastoma (GBM), the most common and lethal aggressive brain tumor in adults, usually becomes refractory to standard-of-care treatments that include surgery, irradiation, and temozolomide (TMZ) chemotherapy. Histone deacetylase 6 (HDAC6) is a therapeutic target in non-central nervous system (CNS) cancers that is receiving increasing scrutiny in GBM [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. Compared to other HDACs, HDAC6 expression is disproportionately high in GBM [ 1 , 3 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations